The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/hep.27770
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter experience using simeprevir and sofosbuvir with or without ribavirin to treat hepatitis C genotype 1 after liver transplant

Abstract: Treatment with an all-oral interferon-free antiviral regimen using simeprevir and sofosbuvir with or without ribavirin (RBV) for 12 weeks resulted in high sustained virologic response (SVR) rates along with minimal adverse events in non-liver transplant (LT) patients with hepatitis C virus (HCV) genotype 1 infection. This is the first multicenter report on the efficacy, safety, and tolerability of this regimen in LT recipients. A total of 123 patients (76% male, 74% white, 60% genotype 1a, 30% METAVIR F3-F4, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
148
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(177 citation statements)
references
References 20 publications
21
148
0
8
Order By: Relevance
“…Several studies have been published recently on sofosbuvir-based regimens combined with other DAAs in transplant recipients with genotype 1 infection. SVR rates at 12 weeks post-treatment were consistently higher than 85% (9,10).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have been published recently on sofosbuvir-based regimens combined with other DAAs in transplant recipients with genotype 1 infection. SVR rates at 12 weeks post-treatment were consistently higher than 85% (9,10).…”
Section: Discussionmentioning
confidence: 82%
“…These results were surpassed by other more effective combinations such as sofosbuvir and simprevir [9] or sofusbuvir and daclatasvir [10].…”
Section: Introductionmentioning
confidence: 93%
“…32 The authors demonstrated an overall SVR of 90% with minimal adverse effects. Of the 123 patients, 98 received sofosbuvir and simeprevir and 25 had the addition of ribavirin.…”
Section: Compensated Liver Diseasementioning
confidence: 87%
“…32 Sixty-one patients with HCV genotype 1 were treated with sofosbuvir and simeprevir for 12 weeks; 3 of these patients also received ribavirin. 27 12 wk 96%-98% (NC and Child-Pugh class A) Need for ribavirin 85%-88% (Child-Pugh class B) 60%-75% (Child-Pugh class C) 3-D + ribavirin 34 24 34 Dosage modifications of calcineurin inhibitors were based on blood levels.…”
Section: Compensated Liver Diseasementioning
confidence: 99%
“…Authors of this trial demonstrated high efficacy with an overall SVR-12 rate of 97%, which is comparable with our experience in patients with milder recurrent HCV infection. A recent study in which 12 patients with recurrent HCV after liver transplantation received sofosbuvir with and without RBV concluded that optimal outcomes require initiation of treatment before decompensation [30]. Based on that we recommend initiating AVT in mild disease to get maximum outcome in LT recipients.…”
Section: Discussionmentioning
confidence: 97%